Perceived emotional intelligence in university students in times of Covid-19: a contribution to the mental health (Journal on studies and research of academic knowledge, 2021)
The aim of the study was to analyze the dimensions of the perceived emotional intelligence of students of the National University of Itapúa, Paraguay, as a contribution to their mental health in times of COVID-19. Quantitative methodology, descriptive-correlational design and probabilistic sampling. The sample population (N=224) included students from the Faculties of Humanities and Medicine. The instrument applied was TMMS-24, whose results showed that 59.8% of the students have an adequate emotional perception, 57.7% have an adequate emotional understanding and 58% have an adequate emotional regulation. And as factors that contribute to their mental health in times of COVID-19 they have manifested positive attitude, self-esteem, physical activity, emotional support, recreation, empathy, self-control, good habits. The perceived emotional dimensions and mental health factors have contributed to them as a means of coping with the COVID-19 pandemic.
Keywords: emotional intelligence; mental health; students; COVID-19; National University of Itapúa